PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH PROVINSI SULAWESI TENGAH - Anita Sosang; Mustainah M.; Muhammad Nawawi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is to analyze the magnitude of the partial and simultaneous influence of work motivation on employee performance at the Central Sulawesi Province Regional Development Planning Agency. This type of research is explanatory or explanatory research. The technique for determining the number of samples was using the Slovin formula, and the number of samples used was 115 respondents, and the technique for determining the sample in this research was through the Purposive Sampling technique. For data collection techniques through observation, library research (Library Research), and field studies (Field Research). Data analysis was carried out through validity tests, reliability tests, normality tests, multicollinearity tests, descriptive analysis, multiple linear regression and hypothesis testing. The research results show that partially work motivation through the dimensions of need for achievement, need for affiliation, and need for power have a significant effect on the performance of Bappeda employees of Central Sulawesi Province. where the resulting coefficient for the need for achievement dimension is 1.163, the need for affiliation is 0.654, and the need for power is 0.843. Apart from that, simultaneously work motivation through the dimensions of need for achievement, need for affiliation, and need for power also have a significant influence on the performance of Central Sulawesi Province Bappeda employees, where the results of the determinant coefficient analysis (R2) show that work motivation has an influence of 86.12%, while the remaining 13.88% is influenced by other factors, of course this result shows that the influence of work motivation on the performance of Central Sulawesi Province Bappeda employees is at a very strong level of influence.